EVALUATION OF NEW CONSERVATIONIST TOOL OF SOIL TILLAGE FOR IMPROVEMENT OF SEEDING IN SMALL FARM - Maciel, Antonio J. S.; Albiero, Daniel (Revista Brasileira de Engenharia de Biossistemas, 2007)
The conservationist tillage is used for erosion control in every world. The system of tillage more efficient it is the No-Till, that maintain the maximum residual covering overthe surface, however the no-tillage have some disadvantages, for instance: it needs seed furrow further affecting the development of the plant’s roots, and the fertilizer distribution, decreasing the yield; the no-tillage uses heavy construction machinery generating more power consumption, and rather soil compaction; and the weed control depends of herbicides. This research evaluates a new rotary tiller named Rotary Paraplow, which objective was to eliminate the found disadvantages, and its conceptinvolves the fusion between a rotary tiller and a Paraplow, using the power take off(PTO) of a small tractor. The new tool it is very light. Several geometries of RotaryParaplows were selected for the study, which had been carried out in tests in laboratoryand in field, with a power tiller of 9 kW, and a small tractor of 40 kW. This new toolshowed a good operational performance.